Loss of Parkin Results in Altered Muscle Stem Cell Differentiation during Regeneration - Esteca, Marcos (2020)
The high capacity of the skeletal muscle to regenerate is due to the presence of muscle stem cells (MuSCs, or satellite cells). The E3 ubiquitin ligase Parkin is a key regulator of mitophagy and is recruited to mitochondria during differentiation of mouse myoblast cell line. However, the function of mitophagy during regeneration has not been investigated in vivo. Here, we have utilized Parkin deficient (Parkin(-/-)) mice to investigate the role of Parkin in skeletal muscle regeneration. We found a persistent deficiency in skeletal muscle regeneration in Parkin(-/-) mice after cardiotoxin (CTX) injury with increased area of fibrosis and decreased cross-sectional area (CSA) of myofibres post-injury. There was also a significant modulation of MuSCs differentiation and mitophagic markers, with altered mitochondrial proteins during skeletal muscle regeneration in Parkin(-/-) mice. Our data suggest that Parkin-mediated mitophagy plays a key role in skeletal muscle regeneration and is necessary for MuSCs differentiation.